2016
DOI: 10.1021/acs.nanolett.6b01713
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution p-Type Metal Oxide Semiconductor Nanowire Array as an Ultrasensitive Sensor for Volatile Organic Compounds

Abstract: The development of high-performance volatile organic compound (VOC) sensor based on a p-type metal oxide semiconductor (MOS) is one of the important topics in gas sensor research because of its unique sensing characteristics, namely, rapid recovery kinetics, low temperature dependence, high humidity or thermal stability, and high potential for p-n junction applications. Despite intensive efforts made in this area, the applications of such sensors are hindered because of drawbacks related to the low sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 45 publications
1
113
0
Order By: Relevance
“…The MOS measures the change in the electrical resistance of the device upon an interaction with the target analyte. Recently, Cho et al demonstrated a patterned p-type polycrystalline MOS nanowire array with an improved sensitivity and response time toward various volatile organic compounds (VOCs) [23], and Katwal et al fabricated a novel zinc oxide nanowire–nanotube hybrid-based sensor with a good response to specific VOCs that serve as markers for breast cancer [24]. Similarly, various other studies demonstrated the outstanding sensing potential of MOS technology for VOC detection [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The MOS measures the change in the electrical resistance of the device upon an interaction with the target analyte. Recently, Cho et al demonstrated a patterned p-type polycrystalline MOS nanowire array with an improved sensitivity and response time toward various volatile organic compounds (VOCs) [23], and Katwal et al fabricated a novel zinc oxide nanowire–nanotube hybrid-based sensor with a good response to specific VOCs that serve as markers for breast cancer [24]. Similarly, various other studies demonstrated the outstanding sensing potential of MOS technology for VOC detection [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…They are induced from the adsorption and desorption of the gases when specific gases interact with its surface, which is affected by three basic factors, namely the transducer function, utility factor, and receptor function [17,18,19]. For these reasons, various chemoresistive gas sensors with large surface-area-to-volume ratios such as nanotubes [20,21,22], nanobamboos [23], nanowalls [24], nanospheres [25,26], and nanocolumns [27] have been studied based on the three basic factors to enhance the gas-sensing properties. Further, it is well known that highly ordered one-dimensional nanostructures, which show extremely large surface-to-volume ratios, are the most promising material platform for a good gas-sensing performance due to the excellent accessibility of target gases and aggregation-free geometry [19].…”
Section: Introductionmentioning
confidence: 99%
“…

A semiconducting metal oxide (SMO) chemiresistor (ZnFe 2 O 4 ) is used for discriminating two isomeric volatile organic compounds (VOCs), namely 1-and 2-propanol. [7][8][9][10] Unlike physisorption based charge transfer sensors, semiconducting metal oxide (SMO) based chemiresistors are mostly operative at high temperature and their resistance/conductance changes in exposure to reducing gases or vapors. The changes in transient current of the ZnFe 2 O 4 chemiresistor are measured at different temperatures (260-320°C) for detecting equal concentrations (200 ppm) of the two structural isomers of propanol.

…”
mentioning
confidence: 99%
“…The changes in transient current of the ZnFe 2 O 4 chemiresistor are measured at different temperatures (260-320°C) for detecting equal concentrations (200 ppm) of the two structural isomers of propanol. [4][5][6][7][8][9]15] In the present work, we have studied the response of ZnFe 2 O 4 based SMO chemiresistor towards equal concentrations (200 ppm) of two isomeric VOCs namely 1-propanol and 2-propanol at four different operating temperatures (i. e. 260, 280, 300 and 320°C). First-principles calculations and kinetic studies on the interaction of 1-and 2propanol over ZnFe 2 O 4 provide further insight in support of the experimental evidence.…”
mentioning
confidence: 99%
See 1 more Smart Citation